“Estudio tecnico – economico social para la instalacion del servicio del comedor en la ciudad universitaria de la UNSM - Buleje Gómez, Alejandro Cesar (2004)
This project studies the installation of a dining room, on the campus of the National University of San Martin Tarapoto, with the purposes of providing the university con1u11idad adequate food both in quantity and nutritional quality, well, with the implementation of project will contribute to creating a source of work. Chapter II contains the market study both the raw material and the final product that determines the size of the plant room, based on the unmet demand for rations, the level of sales and availability of raw materials and inputs . The study of the raw material has been effected by food items (fruits, vegetables, milk, eggs, meat, poultry, fish, tubers, plantains, rice, etc.) and the study of the final product with daily rations. In capitulas III, the size and location of the project is determined, the planned size ratio, raw material availability, investment is made, quantitative analysis, quantitative factors and microlocacionales is also performed. The room size is set to 900 diners a day, equivalent to 900 breakfasts, 900 lunches and 900 dinners, which makes 176,400 rations a year in two shifts of 8 hours each. The location will be at the City University of UNSMs, by such considerations and the previous location established by the Investment Program of the UNSMs. Chapter IV deals concerning the Project Engineering pointing nutritional parameters to be used in the formulations of rations that come to be the technological specifications of the final product and the type of machinery and process equipment is also indicated in the paintings materials required for the proper functioning of the plant is detailed. drain, steam and propane - calculating various electrical, water is also effected. Chapter V is referred to Econónú.co and financial aspect of the project, the value of investments for the operation of dining well the economic and financial evaluation of the project is determined. For civil works it has a budget of S / 546.452, and in equipment and facilities for steam and gas s / 412.987 constitutes 34.60%. The total cost of investment in Tangibles is S / 1051.511 which is the 88.08% in intangible is S /. 52.726, being a 4.69% two investments provide the total fixed investment of S / 1'104, 237 representing 92.03% of the total investment of the project. Working capital is S /. 89.517, which is 50% 7. The total investment of the project reaches the sum of S /. 1 '193.754 is 100%. Sustainability analysis shows in its four project feasibility considerations. The index sensitivity of the project details we having sensitivity against the change in the number of diners indicating that only increased attention by oak 180 diners a day., The project is viable. The sensitivity analysis based on the increased costs, shows that the project has no substantial changes to an increase in the cost of the ratio C / E. Project organization is in Chapter VI, this organization will be based on the rules of procedure of the University Eater UNSMs., Approved by Rectoral Resolution No. 231-97-UNSJvf / R. dated May 6, 1997 which contains staff functions and structural organization chart adopted the project.